A Modified Controlled Cortical Impact Technique to Model Mild Traumatic Brain Injury Mechanics in Mice - Chen, YungChia; Mao, Haojie; Yang, King H.; Abel, Ted; Meaney, David F. (Frontiers in Neurology, 2014)
For the past 25 years, controlled cortical impact (CCI) has been a useful tool in traumatic brain injury (TBI) research, creating injury patterns that include primary contusion, neuronal loss, and traumatic axonal damage. However, when CCI was first developed, very little was known on the underlying biomechanics of mild TBI. This paper uses information generated from recent computational models of mild TBI in humans to alter CCI and better reflect the biomechanical conditions of mild TBI. Using a finite element model of CCI in the mouse, we adjusted three primary features of CCI: the speed of the impact to achieve strain rates within the range associated with mild TBI, the shape and material of the impounder to minimize strain concentrations in the brain, and the impact depth to control the peak deformation that occurred in the cortex and hippocampus. For these modified cortical impact conditions, we observed peak strains and strain rates throughout the brain were significantly reduced and consistent with estimated strains and strain rates observed in human mild TBI. We saw breakdown of the blood-brain barrier but no primary hemorrhage. Moreover, neuronal degeneration, axonal injury, and both astrocytic and microglia reactivity were observed up to 8 days after injury. Significant deficits in rotarod performance appeared early after injury, but we observed no impairment in spatial object recognition or contextual fear conditioning response 5 days and 8 days after injury, respectively. Together, these data show that simulating the biomechanical conditions of mild TBI with a modified cortical impact technique produces regions of cellular reactivity and neuronal loss that coincide with only a transient behavioral impairment.